MEREFLEKSIKAN TUHAN DALAM PERSPEKTIF METAFISIKA, DAN RELEVASINYA BAGI MULTIKULTURALISME INDONESIA - Agustinus Wisnu Dewantara (Bahasa Indonesia, 2018)
Talking about God can not be separated from the activity of human thought. Activity is the heart of metaphysics. Searching religious authenticity tends to lead to a leap in harsh encounter with other religions. This interfaith encounter harsh posed a dilemma. Why? Because on the one hand religion is the peacemaker, but on the other hand it’s has of encouraging conflict and even violence. Understanding God is not quite done only by understanding the religion dogma, but to understand God rationally it is needed. It is true that humans understand the world according to his own ego, but it is not simultaneously affirm that God is only a projection of the human mind. Humans understand things outside of himself because no awareness of it. On this side of metaphysics finds itself. Analogical approach allows humans to approach and express God metaphysically. Human clearly can not express the reality of the divine in human language, but with the human intellect is able to reflect something about the relationship with God. Analogy allows humans to enter the metaphysical discussion about God. People who are at this point should come to the understanding that God is the Same One More From My mind, The Impossible is defined, the Supreme Mystery, and infinitely far above any human thoughts.